2022
DOI: 10.1002/maco.202113022
|View full text |Cite
|
Sign up to set email alerts
|

In situ growth process and corrosion resistance of a layered double‐hydroxide film on an LA103Z magnesium–lithium alloy

Abstract: A layered double‐hydroxide (Mg–Al LDH) film was grown in situ on an LA103Z magnesium alloy in an aluminum nitrate solution at 90°C by adjusting the hydrothermal reaction time. The Mg–Al LDH film comprised Mg–Al LDH and Mg(OH)2, which was obtained after hydrothermal treatment for 24 h, and was thick and dense, with a uniform and compact LDH sheet growing perpendicular to the surface. The LDH sheet showed the best corrosion resistance, and both the Rp and icorr values were two orders of magnitude higher than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…According to the results, the 𝐼 𝑐𝑜𝑟𝑟 values of bare AZ91 and three steam coatings can be ranged in decreasing order: bare AZ91 > 150 ℃+3 h > 150 ℃+6 h >150 ℃+9 h. The Icorr values of steam coatings decreased by 3-4 orders of magnitude relative to the bare AZ91, and the Ecorr values slightly moved in the positive direction. The lower the Icorr value and the greater the Ecorr value is, the better the corrosion resistance of the coating gets [9]. The results showed that the corrosion resistance of AZ91 alloy can be improved significantly by the steam coatings.…”
Section: Resultsmentioning
confidence: 95%
“…According to the results, the 𝐼 𝑐𝑜𝑟𝑟 values of bare AZ91 and three steam coatings can be ranged in decreasing order: bare AZ91 > 150 ℃+3 h > 150 ℃+6 h >150 ℃+9 h. The Icorr values of steam coatings decreased by 3-4 orders of magnitude relative to the bare AZ91, and the Ecorr values slightly moved in the positive direction. The lower the Icorr value and the greater the Ecorr value is, the better the corrosion resistance of the coating gets [9]. The results showed that the corrosion resistance of AZ91 alloy can be improved significantly by the steam coatings.…”
Section: Resultsmentioning
confidence: 95%
“…1,2 They have been seen as ideal materials for aerospace industries, medical equipments, and other fields. 3 Unfortunately, the active chemical properties conduce to poor corrosion resistance, which extremely hinders their development and application. 4,5 At present, it is the most cost-effective approach to prepare a protective film on the surface of magnesium alloys for improving its corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As the lightest structural material, magnesium–lithium (Mg–Li) alloys have a series of excellent properties such as low density, high specific strength, good electromagnetic shielding, and other excellent comprehensive performance 1,2 . They have been seen as ideal materials for aerospace industries, medical equipments, and other fields 3 . Unfortunately, the active chemical properties conduce to poor corrosion resistance, which extremely hinders their development and application 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] It was found that LDH can be applied in metal corrosion protection due to its interlayer anion exchangeable, physical barrier, and self-healing properties. [7][8][9] Huang et al [10] gained MgAl-LDH films on AZ31 substrates by hydrothermal method and then modified with sodium laurate (SL) and sodium dodecyl benzene sulfonate (SDBS). The experimental results suggested that the modified films could effectively improve the long-term corrosion resistance of magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%